‘We look after our own’: The cultural dynamics of celebrity in a small country - Lyn Barnes (Asia Pacific Network, 2013)
Unlike the United Kingdom, the United States and Australia, where celebrities are often subjected to derision in the tabloid media, the New Zealand Woman’s Weekly, the country’s longest-running women’s magazine, respects and values its local celebrities. A content analysis of cover lines on the magazine over the past eight decades reveals that although the magazine has adhered to a steadfast formula of celebrating mothers and wives, there has been a steady shift to a focus on the love lives and scandals of foreign celebrities. More recently, however, the magazine has turned its attention to well-known New Zealanders and developed its own brand of celebrity news.